Antioxidant properties of raw garlic (Allium sativum) extract - Rahman, Md. Mokhlesur; Fazlic, V.; Saad, N. W. (UPM, 2012)
Garlic has been a favorite additive in food for many years in various cultures. It is known that garlic (Allium sativum) possesses antimicrobial, antiprotozoal, antimutagenic, antiplatelet and antihyperlipidemic properties. Allicin, a thiosulfinate extract of garlic, has been presumed to be a very strong antioxidant. High performance liquid chromatography (HPLC) analysis of raw garlic extract was not conclusive to determine allicin’s presence. However, using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging methods to determine the antioxidant activity of raw garlic extract shows a color change from deep violet to yellow, indicating antioxidant activity. Thus, raw garlic can be a source of antioxidant based on the results of the DPPH scavenging analysis.